Desempenho e concentrações hormonais de novilhas Nelore e ½ Girolando ½ Nelore criadas em sistemas de integração pecuária floresta - Duarte, Julia Paschoareli Ferro [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Considering the negative effects of heat stress on animal production, the provision of shade is very eficiente to improve the animal comfort and trees are the best and most economical resources to provide better welfare to animals. The objective of the study was to evaluate the performance and hormonal parameters of Nellore and ½ Girolando and ½ Nelore heifers in an integrated livestock-forest system with 187 trees/ha and Nelore heifers in conventional system (without trees). The experimental design was completely randomized with three treatments and five repetitions. The treatments were: Nelore heifers in integrated livestock forestry system, with eucalyptus planted in single lines at a density of 187 trees / ha; Heifers from the crossing of ½ Nelore ½ Girolanda in integrated livestock forestry, with eucalyptus planted in single lines at a density of 187 trees / ha; Nelore heifers in conventional system in full sun, without the presence of trees. We used heifers with an average age of 11 months and an average initial weight of 261 kg. Average daily weight gain, total protein, albumin, globulin, cortisol, triiodothyronine (T3) and thyroxine (T4) were evaluated. Data were submitted to analysis of variance and Tukey's test at 5% probability. Albumin, globulin and total protein concentrations were lower in Nelore animals kept in SC. The hormones T3 and T4 showed no difference between treatments. Cortisol levels were higher in Nellore animals kept in the sun. No differences were observed in weight gain. The integration system livestock forest provides lower temperatures and consequently better thermal comfort in the hottest hours of the day, than the conventional system. The greater thermal comfort did not alter the daily weight gain of heifers, but heifers that were in the conventional system, without the presence of trees, showed changes in blood and hormonal parameters.

Considerando os efeitos negativos do estresse térmico à produção animal, a oferta de sombra é muito eficiente para melhorar o conforto térmico dos animais, sendo as árvores os melhores e mais econômicos recursos para fornecer melhor bem-estar aos animais. O objetivo do trabalho foi avaliar as variáveis microclimáticas em sistema de integração pecuária floresta com 187 árvores/ha e sistema convencional (sem o componente arbóreo), bem como desempenho e parâmetros hormonais de novilhas Nelore e ½Girolando e ½ Nelore em sistema de integração pecuária floresta com 187 árvores/ha e sistema convencional. O delineamento experimental foi inteiramente ao acaso com três tratamentos e cinco repetições. Os tratamentos foram: Novilhas Nelore em sistema de integração pecuária floresta, com eucaliptos plantados em linhas simples na densidade de 187 árvores/ha; Novilhas oriundas do cruzamento de ½ Nelore ½ Girolando em integração pecuária floresta, com eucaliptos plantados em linhas simples na densidade de 187 árvores/ha; Novilhas Nelore em sistema convencional a pleno sol, sem a presença de árvores. Foram utilizadas novilhas com idade média de 11 meses e peso médio inicial de 261 kg. Foram avaliados ganho de peso médio diário, proteína total, albumina, globulina, cortisol, triiodotironina (T3) e tiroxina (T4). Os dados foram submetidos à análise de variância e teste de Tukey a 5% de probabilidade. A temperatura foi menor e a umidade relativa foi maior no sistema IPF. As concentrações de albumina, globulina e proteína total foram menores nos animais da raça Nelore mantidos em SC. Os hormônios T3 e T4 não apresentaram diferença entre os tratamentos. Os níveis de cortisol foram maiores nos animais Nelores mantidos ao sol. Não foram observadas diferenças no ganho de peso. O sistema de integração pecuária floresta proporciona menores temperaturas e consequentemente melhor conforto térmico nas horas mais quentes do dia, que o sistema convencional. O maior conforto térmico não alterou o ganho de peso diário das novilhas, mas as novilhas que estavam no sistema convencional, sem a presença de árvores, apresentaram alterações nos parâmetros sanguíneos e hormonais.
Performance and hormone concentrations of Nelore and ½ Girolando ½ Nelore heifers raised in integrated livestock-forestry systems
Keywords: Thermal comfort; Animal welfare; Silvipastoral system; Thermal stress; Cattle; Cortisol; Crossbreeding; Conforto térmico; Bem-estar animal; Sistema silvipastoril; Estresse térmico; Bovinos; Cortisol; Cruzamento